2022
DOI: 10.3390/ijerph19010533
|View full text |Cite
|
Sign up to set email alerts
|

The Social and Natural Environment’s Impact on SARS-CoV-2 Infections in the UK Biobank

Abstract: COVID-19 has caused a global pandemic with considerable impact. Studies have examined the influence of socioeconomic status and air pollution on COVID-19 risk but in low detail. This study seeks to further elucidate the nuances of socioeconomic status, as defined by the Index of Multiple Deprivation (IMD), air pollution, and their relationship. We examined the effect of IMD and air pollution on the likelihood of testing positive for SARS-CoV-2 among 66,732 UKB participants tested for SARS-CoV-2 from 16 March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Some studies reported resolutions up to 100m 2 (28,31), others used entire cities (29) or monitoring stations spaced tens of kilometres apart (32,37). Several did not specify PM 2.5 resolution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies reported resolutions up to 100m 2 (28,31), others used entire cities (29) or monitoring stations spaced tens of kilometres apart (32,37). Several did not specify PM 2.5 resolution.…”
Section: Resultsmentioning
confidence: 99%
“…While this sample is large at around 500,000 people, it is not considered representative of the UK population due to low participation rates and a skew towards older persons (38,39). Additionally, three used PM 2.5 estimates from 2010 (24,27,31) – a decade old – and all used participant residences from 2006-2010. This does not account for change of address or the steady decline in PM 2.5 in the interim (40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing duplicates, N = 732 were assessed for inclusion (abstract and title review). Finally, 46 original research articles were considered eligible [ 25 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] Table 1 . Data from screening and extraction is available ( Supplementary Tables S1–S3 ).…”
Section: Results/synthesismentioning
confidence: 99%